Is there a safe dental plaque index to prevent periodontal diseases related to plaque? A systematic review and meta-analysis. (Research, Society and Development, 2022)
Periodontitis is a chronic multifactorial inflammatory disease associated with a dysbiotic biofilm and characterized by progressive destruction of the tooth-supporting apparatus. This systematic review aimed to establish the quantitative association between dental plaque index and plaque-induced periodontal outcomes, as well as, clinical plaque index (PI) cut-off points. MEDLINE electronic searches were performed with at least two outcomes (healthy, G or P). 124 articles met the eligibility criteria and were included in meta‐analysis. Healthy (H) group had a PI three times lower than G group (ROM 3.21; 95% CI 2.35-4.39) and P group (ROM 3.34; 95% CI 2.97-3.76); P group had 32% higher PI than G group (ROM 1.32; 95% CI 1.15-1.50). The meta‐analyses of different PI (Silness and Löe, PI-SL; and percentage of faces, PI-%), PI-SL H group (MRAW 0.52) differed from G group (MRAW 1.58) and P group (MRAW 1.83) although it was not possible to distinguish the G group (95% CI 1.28-1.89) from the P group (95% CI 1.67-1.98). This was also observed in the PI-% (MRAW 22% H, MRAW 68% G and P group). PI was able to distinguish periodontal health individuals from whom with periodontal conditions associated with plaque. This systematic review proposes the following PI values cutoff points: H group lower than 0.7 (PI-SL), 30% (PI-%); G group 0.7 to 1.6 (PI-SL) or 31% to 60% (PI-%); and P group up to 1.6 (PI-SL) or 60% (PI-%). The results have clinical application on health promotion and disease prevention through population-based interventions.